2012
DOI: 10.1590/s0102-695x2012005000088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extraction and transesterification methods on the determination of the fatty acid contents of three Brazilian seaweed species

Abstract: Seaweeds are photosynthetic organisms important to their ecosystem and constitute a source of compounds with several different applications in the pharmaceutical, cosmetic and biotechnology industries, such as triacylglycerols, which can be converted to fatty acid methyl esters that make up biodiesel, an alternative source of fuel applied in economic important areas. This study evaluates the fatty acid profiles and concentrations of three Brazilian seaweed species, Hypnea musciformis (Wulfen) J.V. Lamouroux (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In contrast, Cavonius et al [29] reported that the Lewis's method showed higher fatty acid recovery from Nannochloropsis oculata and Isochrysis galbana, than B&D's method. Cavonius et al and Martins et al [29,30] suggested that the differences in the algal cell walls could influence the efficiency of various extraction methods. Therefore, it is necessary to select a suitable FAME extraction method for algal species.…”
Section: Comparison Of Fame Extraction Methods For Biodiesel Productionmentioning
confidence: 99%
“…In contrast, Cavonius et al [29] reported that the Lewis's method showed higher fatty acid recovery from Nannochloropsis oculata and Isochrysis galbana, than B&D's method. Cavonius et al and Martins et al [29,30] suggested that the differences in the algal cell walls could influence the efficiency of various extraction methods. Therefore, it is necessary to select a suitable FAME extraction method for algal species.…”
Section: Comparison Of Fame Extraction Methods For Biodiesel Productionmentioning
confidence: 99%
“…Palmitic acid, notably, contained a maximum of 50.16% saturated fatty acid. Another study in this context is that of Martins et al [15], who compared the fatty acid contents and compositions of algal oil extracted from U. lactuca by reference to different extraction methods. The highest oil extraction yields were specifically 2.49 mg/g-dw saturated fatty acid (mainly palmitic acid), 0.79 mg/g-dw mono-unsaturated fatty acid (mainly oleic acid), and 1.09 mg/g polyunsaturated fatty acid.…”
Section: Fatty Acid Composition Of Lipid Extracted From E Intestinalismentioning
confidence: 99%
“…Another recent efficiencyenhancing innovation in lipid extraction is micro-algae pretreatment, either by autoclaving, bead-beating, sonication, osmotic shock, microwave, or other method [10][11][12]. Whereas many lipid extraction methods have been investigated for micro-algae applications [10,11,[13][14][15][16], relatively few have been evaluated for use with macroalgae [12,14,17]. Suganya and Renganthan [12] conducted kinetic studies on algal oil extraction from Ulva lactuca using autoclaving, bead-beating, ultra-sound, osmotic shock, and microwave pretreatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used by several authors. 124 Martins et al, 124 makes a comparison between this method and the one that uses Bf3/MeOH, to later determine the fatty acids by GC in three species of Brazilian algae. When comparing the fatty acid contents in the species; when the transesterification was performed by the B&D-BF 3 method, S. cymosum and H. musciformis showed the highest and lowest fatty acid contents, respectively.…”
Section: Main Derivatization Methods Usedmentioning
confidence: 99%
“…123,132 Compared to the BF 3 /MeOH method, with the KOH/MeOH method the latter is more effective, simpler, less laborious, and easier to handle. 132 According to Martins et al, 124 this method produces false results due to the high matrix effect it presents. NaOH-Methanol: Guil-Guerrero et al, 137 used a method in which the fish oil samples were mixed with a solution of methanol and acetyl chloride (20: 1, v/v) and 20 mL of hexane, previously described by Rodríguez-Ruiz et al 138 An alternative to this method is a mixture of NaOH-methanol and hexane, for the preparation of the methyl esters, however the BF 3 /MeOHreagent is used as a catalyst, 139 although this procedure has been used by several authors.…”
Section: H 2 So 4 -Methanolmentioning
confidence: 99%